FRI0253 Eosinophilic fasciitis: retrospective evaluation of 7 cases. (1st June 2001) - Tunc, E; Inal, V; Keser, G; Pirildar, T; Türk, T; Aksu, K; Kabasakal, Y; Oksel, F; Doganavsargil, E
Abstract : Background: Eosinophilic fasciitis (EF) is a rare disorder characterised by scleroderma-like enduration of the skin, predominantly on the extremities and peripheral eosinophilia. Absence of Raynaud's phenomenon and visceral involvement are typical features. Histologic findings include fibrosis of muscle fascia and eosinophilic infiltration. Different clinical entities are reported in association with EF. Hereby, we aimed to present clinical characteristics of our cases. Objectives: The medical data of 7 patients with EF (F/M:4/3; mean age 41.7 ± 19), who were followed up for 22.7 ± 19.6 months in Ege University Rheumatology department between January 1996 and December 2000. Mean disease duration was 11 ± 9.2 months on initial diagnosis. The diagnosis was made by en-block biopsy. Skin enduration was located on the lower and upper extremities in all cases. In one patient there was additional enduration on trunk. All cases had peripheral eosinophilia and hypergammaglobulinemia. Elevated muscle enzymes were present only in one case. High titer ANA positivity was present only in three female cases. 2 cases had carpal tunnel syndrome, one had interstitial eosinophilic pneumonia, one had pericarditis and Hashimato thyroiditis, one had vitiligo, one had type II DM which began simultaneously and one had psoriasis in association with EF. There were no history of any relevant medication and toxic material ingestion. No one had malignancy in the follow-up period. Initial treatment consisted of methylprednisolone (32 mg/day) and methotrexate (10 mg/week). Since in literature, high serum histamin levels and good response to H2 blockers were reported, ranitidine was also added to this treatment1. All the patients responded well; however one case was resistant to this treatment. D-penicillamine (150 mg/day) and colchicine (1 mg/day) treatment were added for this patient. Skin endurations regressed in all cases. Two patient had complete and the other five had partial remission. Methods: Results: Conclusion: In conclusion, the diagnosis of EF should be always confirmed by en-block biopsy and presence of associated autoimmune pathologies should be kept in mind and searched. Malignancy should always be excluded. Response to appropriate treatment is generally satisfactory. Reference: Naschitz JE, Boss JH, Misselevich I, Yesfurun D, Rosner I. The fasciitis-panniculitis syndromes. Clinical and pathologic features. Medicine (Baltimore) 1996;75(1):6–16